Effect of Turbulent Oil Film on the Dynamic Characteristics of 2-lobe Journal Bearings - STRZELECKI, Stanislaw Kazimierz (Engineering Transactions, 2025)
Turbogenerators in power plants utilize two-lobe journal bearings, which can carry large loads with good stability at the speeds typically encountered in the power industry. These bearings feature the profiles such as elliptical, offset, cylindrical or pericycloidal. The design of these bearings ensures proper load capacity, favorable thermal conditions for the oil film, and stable operation of the associated turbounits. However, the design of these bearings should be supported by calculations that account for turbulence generated in the oil film. This paper presents the results of dynamic characteristic calculations for four types of two-lobe journal bearings operating under adiabatic laminar or turbulent flow conditions in the lubricating gap. The dynamic characteristics, expressed as the stiffness and damping coefficients of the oil film, were obtained using the perturbation method. Stability ranges for a simple symmetric rotor were determined for the considered bearings. A numerical algorithm for the iterative solution of the Reynolds, energy and viscosity equations was employed to calculate the oil film forces, which formed the basis for the bearing’s dynamic characteristics. These investigations were carried out assuming the static equilibrium position of the journal.